Development of therapeutic peptide producers based on Escherichia coli BL21 and their cultivation technology - Z. R. Khasanshina; I. A. Kornakov; E. A. Buslaeva; A. V. Kazakova; S. A. Ishchuk; V. I. Shmurak; V. B. Saparova; V. F. Latypov; R. V. Drai (Разработка и регистрация лекарственных средств)
Introduction. Peptides with a molecular weight of less than 5 kDa have been used in medicine and biotechnology over the past decade for the treatment of various diseases. However, chemical synthesis peptide has several disadvantages, including low yield, reduced efficiency, and high costs. An alternative approach to peptide production is the use of the Escherichia coli expression system. The development of effective peptide synthesis technology remains a critical task because of the low productivity of recombinant strains.Aim. Developing highly efficient strains of Escherichia coli BL21 expressing therapeutic peptides with a molecular weight of less than 5 kDa in E. coli and their cultivation technology.Materials and methods. Genetic constructs were obtained using the restriction-ligase method, and their authenticity was confirmed by Sanger sequencing. Cultivation technology was developed using the Design of Experiments approach. The cultivation condition was validated in the Biostat B bioreactor. Hybrid proteins were purified by metal-chelate chromatography, followed by hydrolysis ULP proteas to obtain the target peptides. The quantitative content of the target protein was determined by capillary electrophoresis, and the authenticity of the protein was confirmed by HPLC-MS and ELISA.Results and discussion. Highly efficient peptide-producing strains were developed. Cultivation conditions were optimized: рН 7.5 ± 0.5, cultivation temperature 37 °C, induction optical density 28 ± 2, IPTG concentration 0.05 мМ. The productivity of the producer strains was up to 4.82 ± 0.05 g/L. Furthermore, samples of the target peptides were isolated and purified.Conclusion. The productivity of peptides in this study were significantly higher than in previous research. The presented strategy for strain development, cultivation and purification technology can be used production of therapeutic peptides with diverse physical chemicals characteristics in the future.